Late Quaternary neotectonics in the Bird's Head Peninsula (West Papua), Indonesia: Implications for plate motions in northwestern New Guinea, western Pacific. (15th September 2022) - Eka Adi Saputra, Sukahar; Fergusson, Christopher L.; Dosseto, Anthony; Dougherty, Amy; Murray-Wallace, Colin V.
Graphical abstract: Highlights: 230 Th–U ages (2.7–246 ka) date emergent coral reefs in northwestern New Guinea. Rapid uplift rates of up to 1.28 m/ka are indicated. Rapid uplift reflects oblique subduction along the Manokwari Trough. Late Cenozoic neptunian dykes are probably gravity related. Abstract: New Guinea is a mountainous island in a tectonically active setting with regions experiencing rapid uplift rates as shown by the celebrated emergent coral reef terraces of the Huon Peninsula. In the northern Bird's Head Peninsula of northwestern New Guinea, rapid uplift has been a feature of the tectonic history over the past 2.7 Ma with the development of the mountainous and highly dissected Kemum High (up to 2200 m) associated with the formation of the Central Bird's Head Monocline, implying a long-term uplift rate approaching 0.8 m/ka. In this work, Late Quaternary uplift rates of up to 1.28 m/ka were determined for emergent coral reefs in the Manokwari region (northeast of the much larger Kemum High). The rapid uplift rates are based on 230 Th-U ages (2.7 ± 0.3 to 246.3 ± 8.0 ka with most ages in the range 69–128 ka) on corals and coralline algae, sampled from calcarenites at elevations of 2.45–77.5 m above present sea level. The rapid uplift indicates neotectonic activity reflecting crustal thickening in the Quaternary and neptunian dykes probably related to gravitational instability. The present-day tectonic setting of the Bird's Head Peninsula is cryptic, but the combination of uplift and tectonic activity shown by the earthquakes are consistent with ongoing oblique convergence between the Bird's Head and the adjacent Pacific-Caroline plate. Over the past 2 Ma, plate motion between the Bird's Head Peninsula and the Pacific-Caroline Plate has been accommodated by incipient south-dipping subduction along the Manokwari Trough to the north (with longer-lived subduction along the New Guinea Trench) and sinistral strike-slip movement along the Yapen fault whereas the Sorong Fault has been largely inactive.